1997
DOI: 10.1007/s004649900387
|View full text |Cite
|
Sign up to set email alerts
|

Partial fundoplication for gastroesophageal reflux

Abstract: Partial fundoplication is an excellent treatment for patients with GERD and weak peristalsis, for it corrects the abnormal reflux and avoids postoperative dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…In a series of 107 patients, manometry changed the therapy offered in 10% of patients referred for antireflux surgery (37). Surgeons will often elect to perform a partial fundoplication in patients who have peristaltic dysfunction of the esophagus by manometry (38). These reports suggest, but do not prove, that better reflux control is achieved with a complete (Nissen) fundoplication than with a partial (Toupet) and that in a patient with less effective esophageal peristalsis, the risk of dysphagia is higher with the complete fundoplication.…”
Section: Endoscopy In Gerdmentioning
confidence: 99%
“…In a series of 107 patients, manometry changed the therapy offered in 10% of patients referred for antireflux surgery (37). Surgeons will often elect to perform a partial fundoplication in patients who have peristaltic dysfunction of the esophagus by manometry (38). These reports suggest, but do not prove, that better reflux control is achieved with a complete (Nissen) fundoplication than with a partial (Toupet) and that in a patient with less effective esophageal peristalsis, the risk of dysphagia is higher with the complete fundoplication.…”
Section: Endoscopy In Gerdmentioning
confidence: 99%
“…4 It is obvious that a partial fundic wrap in this setting is preferable to a full wrap, which might result in continued esophageal obstruction. Several studies [5][6][7] have confirmed the usefulness of TF in patients with esophageal dysmotility disorders. In addition, a number of recent reports have demonstrated the efficacy of the procedure in adults with GER disease that is not associated with achalasia or other esophageal motility disorders.…”
Section: Preoperative Evaluation and Treatmentmentioning
confidence: 99%
“…Antireflux surgery is an effective treatment for gastroesophageal reflux disease (GERD), with its complex pathophysiology with good long-term results in the majority of patients, and is superior over medical therapy to control GERD [1][2][3][4][5][6][7]. Therefore, antireflux surgery should be considered in all patients with severe GERD and even in those patients with mild reflux oesophagitis in whom continuous medical treatment with proton pump inhibitors on a standard dose fails to achieve acceptable symptomatic and/or endoscopic results [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, incomplete LES relaxation following the Nissen fundoplication may lead to inability to belch and vomit and may be responsible for postoperative bloating [10][11][12]. Therefore, alternative antireflux procedures, such as partial posterior fundoplication, have been employed in order to decrease postoperative side effects [2,3]. In several institutes a tailored approach of antireflux surgery is applied, with performance of the Nissen fundoplication in the case of normal oesophageal peristalsis and the partial posterior fundoplication in the presence of weak oesophageal peristalsis [4].…”
Section: Introductionmentioning
confidence: 99%